Pollution Characteristics and Risk Assessment of Volatile Organic Compounds in Songhua Lake, China - Zhang, Yu-ting; JIAO, Li-xin; CHENG, Yun-xuan; ZHANG, Yue; YIN, Yu-hua; HUANG, He (International Journal of Scientific Research and Management (IJSRM), 2023)
In order to assess the dangers to human health and the environment from Songhua Lake's volatile organic compounds (VOCs) pollution. A total of 18 VOCs were found in the water samples that were collected at 26 sampling locations in Songhua Lake utilizing the purge and trap technique and gas chromatography-mass spectrometry (GC-MS). Toluene and naphthalene had the highest detection rates among them, reaching 96.15%; trans-1,2-dichloroethylene, 1,2-dichloroethane, and isopropyl benzene had the lowest rates, only 3.85%. The maximum and average concentrations of 1,1-dichloroethane were 20.93 μg/L and 4.16 μg/L, respectively, the maximum concentration of isopropyl benzene was only 0.02 μg/L, and the average concentration was also the lowest. The spatial distribution of VOCs in Song Hua Lake was typically described as "high in the northwest and low in the southeast," with a concentration range of 0.00 to 23.21 μg/L. An examination of the current situation reveals that human activity-related ecological deterioration is the primary cause of the VOCs contamination in Songhua Lake. The results of the risk assessment revealed that there were only moderate ecological risks to aquatic organisms and that the non-carcinogenic and carcinogenic risk indices of Songhua Lake were within the safe range. Additionally, there were no non-carcinogenic or carcinogenic threats to the health of people as a whole.